1999
DOI: 10.1021/je980118j
|View full text |Cite
|
Sign up to set email alerts
|

Static Dielectric Constant and Relaxation Time Measurements on Binary Mixtures of Dimethyl Sulfoxide with Ethanol, 2-Ethoxyethanol, and Propan-1-ol at 293, 303, 313, and 323 K

Abstract: Time domain spectroscopy in reflection mode has been used to determine complex reflection coefficient for 2-ethoxyethanol-dimethyl sulfoxide (DMSO), ethanol-DMSO, and propan-1-ol-DMSO mixtures at 293, 303, 313, and 323 K, in the frequency range of 10 MHz to 10 GHz. Further Fourier transform and least-squares fit methods have been used to obtain the complex permittivity, static dielectric constant, and relaxation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Same type of change in ε 0 values has been observed at all four temperatures under study. Earlier, Khirade et al 16 investigated the molecular dynamics of binary mixture of ethyl alcohol (ethanol) and propan-1-ol with dimethylsulfoxide using dielectric spectroscopy and confirmed that the dielectric constant increases with increase in volume percentage of DMSO (up to 90%) in alcohol, above that it decreases to the corresponding value of pure DMSO. Increase in ε 0 with increase in percentage of DMSO indicates the increase in effective dipole moment (increased polarization) of the system up to 0.7 X DMSO above that effective dipole moment decreases.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Same type of change in ε 0 values has been observed at all four temperatures under study. Earlier, Khirade et al 16 investigated the molecular dynamics of binary mixture of ethyl alcohol (ethanol) and propan-1-ol with dimethylsulfoxide using dielectric spectroscopy and confirmed that the dielectric constant increases with increase in volume percentage of DMSO (up to 90%) in alcohol, above that it decreases to the corresponding value of pure DMSO. Increase in ε 0 with increase in percentage of DMSO indicates the increase in effective dipole moment (increased polarization) of the system up to 0.7 X DMSO above that effective dipole moment decreases.…”
Section: Resultsmentioning
confidence: 90%
“…5, it is observed that the relaxation time values gradually decrease with increase in volume percentage of DMSO in EG. Khirade et al 16 also reported that the relaxation time value gradually decreases with increase in volume percentage of DMSO in ethyl alcohol. EG is derivative of ethyl alcohol in which two hydroxyl groups are attached to the terminal carbon atom of ethane.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The dielectric constant is one of the fundamental properties that must be known to utilize theories of electrolyte solutions [2][3]. The dielectric constant is an important physicochemical parameter, as it is related to many important physical and biological applications [3][4]. The dielectric constant of a solvent is a relative measure of its polarity and its measurements are often used for evaluation of the characteristics of the liquid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al [5] reported the dielectric parameters for aniline-alcohol mixtures using the time domain technique. Dielectric parameters for dimethylsulphoxide-alcohol and dimethylformamide-alcohol mixtures were reported by Khirade et al [6,7] using time domain reflectometry (TDR). Chaudari and Mehrotra [8] reported the dielectric parameters for pyridine-alcohol mixtures using TDR.…”
Section: Introductionmentioning
confidence: 99%